A Smart Contract Blockchain Penetration Testing Framework (Global Journal of Computer Science and Technology, 2023)
Likened to old-style contracts smart agreements motorized by blockchain ensure that deal processes are real safe then well-organized Without the need aimed at third-party mediators like lawyers smart contracts enable transparent processes cost-effectiveness time efficiency and trust lessness While old-style cybersecurity attacks on keen agreement requests can be thwarted by blockchain new threats and attack vectors are constantly emerging which affect blockchain in a manner alike toward additional web and application-based systems Organizations can develop and use the technology securely with connected infrastructure by using effective blockchain testing However the authors discovered throughout the sequence of their investigate that Blockchain technology has security issues like permanent dealings insufficient access and ineffective plans Web portals and other applications do not contain attack vectors like these This study introduces a brand new penetration testing framework for decentralized apps and clever contracts Results from the suggested penetration-testing methodology were com-pared by those from automatic diffusion examination scanners by the authors The findings revealed gaps in vulnerabilities that were not disclosed during routine pen testing
Keywords: smart contracts; attack vectors; cyber-security; blockchain; cyber threats